Comparative assessment of the efficacy and safety of acarbose and metformin combined with premixed insulin in patients with type 2 diabetes mellitus. Issue 35 (September 2017) - Wu, Honghua; Liu, Jie; Lou, Qingqing; Liu, Jing; Shen, Li; Zhang, Mingxia; Lv, Xiaofeng; Gu, Mingjun; Guo, Xiaohui
Abstract : Abstract: This study, a subgroup analysis of the data from the Organization Program of DiabEtes INsulIN ManaGement study, aimed to compare the efficacy and safety profiles of acarbose and metformin used in combination with premixed insulin. This analysis included 80 and 192 patients taking only 1 oral antidiabetic drug, classified into acarbose (treated with acarbose + insulin) and metformin groups (treated with metformin + insulin), respectively. The efficacy and safety data were analyzed for within- and between-group differences. The clinical trial registry number was NCT01338376. The percentage of patients who achieved target hemoglobin A1c (HbA1c) <7% in the acarbose and metformin groups were 38.75% and 30.73%, respectively, after a 16-week treatment. The average HbA1c levels in the acarbose and metformin groups were comparable at baseline and decreased significantly in both groups at the end of the study. All 7 blood glucose decreased significantly in both groups at endpoint compared with that at baseline. Insulin consumption was higher in the metformin group in terms of total daily amount and units/kg body weight. Incidences of hypoglycemia were similar in both groups. Body weight changed significantly in both groups from baseline to endpoint, but with no significant difference between the groups. Mean scores of Morisky Medication Adherence Scale improved in both groups at endpoint. Combination of insulin with acarbose or metformin could improve glycemic control in patients with type 2 diabetes mellitus. Acarbose and metformin were found to be comparable in terms of efficacy, weight gain, and incidence of hypoglycemia.